PENGARUH KOMPETENSI DAN KOMITMEN KERJA TERHADAP KINERJA GURU ASN DI SMA NEGERI 1 PRAJEKAN DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING - Maula, Zhylda Putri Inayatul; Harisandi, Yudhistira; Kusnadi, Edy (Fakultas Ekonomi dan Bisnis, 2022)
Education is a very important element in the progress of the nation, in educational institutions teachers play an important role in the teaching and learning process so that by doing so produce superior and competitive human resources. The purpose of this study was to analyze and test the effect of competence and work commitment on the performance of ASN teachers at SMA Negeri 1 Prajekan with work motivation as an intervening variable. This study uses a quantitative approach. The population in this study were ASN teachers at SMA Negeri 1 Prajekan. Sampling technique using saturated sample. Data analysis and hypothesis testing in this study used the Structural Equation Model – Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that Competence has a significant positive effect on Work Motivation, Work Commitment has a positive significant effect on Work Motivation, Competence has a positive significant effect on ASN Teacher Performance, Work Commitment has a positive but not significant effect on ASN Teacher Performance, Work Motivation has a significant positive effect on the Performance of ASN Teacher Performance, Competence on ASN Teacher Performance through Work Motivation has a significant positive effect, Work commitment on ASN Teacher Performance through Work Motivation has a significant positive effect